Regulasi Zakat dan Pranata Sosial Dalam Upaya Pengentasan Masalah Kemiskinan - Taufik, Muhamad; Irwansyah, Shindu (STAI AL-FALAH CICALENGKA, 2020)
Almost every Eid al-Fitr, thousands of people jostle until several people pass out to fight over zakat mal from a businessman or public official. Poor people risk their lives to get a little money (between 10 thousand and 25 thousand rupiah). This direct distribution of zakat is because the muzaki feel they are more targeted or do not trust the accountability of zakat management institutions. In contemporary economics, zakat has a distributional effect on reducing the income gap between the rich and the poor. Zakat can also stimulate the economic demands of the poor by increasing output and employment. So, if zakat is paid according to the Shari'a, poverty can be eliminated by reducing poor Muslims. Muslims are also encouraged to give donations, such as the establishment of waqf institutions. Waqf institutions can be modified to promote the progress of Muslims and increase their ability to face the challenges of economic globalization. Poverty alleviation requires Muslims to carry out a radical transformation that includes buildings with complete capacities, commitment to cooperation, government political will, and regulation and implementation of the principles of justice in Islam. Keywords: Zakat mal, zakat management institutions Abstrak Hampir setiap menjelang Idul Fitri, ribuan orang berdesak-desakan sampai beberapa orang pingsan untuk berebut zakat mal dari seorang pengusaha dan atau pejabat publik. Warga miskin mempertaruhkan jiwanya untuk mendapatkan sedikit uang (antara 10 ribu sampai 25 ribu rupiah). Pembagian zakat secara langsung ini karena muzaki merasa lebih tepat sasaran atau kurang percaya dengan akuntabilitas lembaga-lembaga pengelola zakat. Dalam ekonomi kontemporer, zakat memiliki dampak distributional untuk mengurangi kesenjangan pendapatan antara golongan kaya dan miskin. Zakat juga dapat menstimulasi tuntutan ekonomi kaum miskin dengan meningkatkan output dan lapangan pekerjaan. Jadi, apabila zakat ditunaikan sesuai syariat, kemiskinan dapat dihilangkan dengan mengurangi umat muslim yang miskin. Umat muslim juga dianjurkan berinfak, seperti pendirian institusi wakaf. Institusi wakaf dapat dimodifikasi untuk mempromosikan kemajuan umat Islam dan meningkatkan kemampuan mereka untuk menghadapi tantangan globalisasi ekonomi. Pengentasan kemiskinan menuntut umat Islam melakukan transformasi radikal yang mencakup bangunan berkapasitas lengkap, komitmen kerjasama, political will pemerintah, serta regulasi dan implementasi prinsip-prinsip keadilan dalam Islam. Kata kunci: Zakat mal, lembaga pengelola zakat